2013
DOI: 10.1371/journal.pone.0080752
|View full text |Cite
|
Sign up to set email alerts
|

The Exosome Cofactor Rrp47 Is Critical for the Stability and Normal Expression of Its Associated Exoribonuclease Rrp6 in Saccharomyces cerevisiae

Abstract: Rrp6 is a conserved catalytic subunit of the eukaryotic nuclear exosome ribonuclease complex that functions in the productive 3’ end maturation of stable RNAs, the degradation of transiently expressed noncoding transcripts and in discard pathways that eradicate the cell of incorrectly processed or assembled RNAs. The function of Rrp6 in these pathways is at least partially dependent upon its interaction with a small nuclear protein called Rrp47/Lrp1, but the underlying mechanism(s) by which Rrp47 functions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 64 publications
6
32
0
Order By: Relevance
“…By monitoring the rescue of the PMA1 mRNA level in different deletion strains, we showed that the targeting and degradation of Rho-induced aberrant mRNPs by Rrp6 is stimulated by the cofactors Rrp47 and Mpp6 as well as the TRAMP complex [13]. An interesting finding made in those studies, which was also reported by others [14][15][16], is that Rrp47 plays an important role in a mutual protein stabilization with Rrp6, highlighting a close physical association between the two protein partners [16]. In effect, removal of one partner by gene deletion induces a depletion of the other partner by more than 90% [13].…”
Section: Rho-based Perturbation Of Mrnp Biogenesis In Yeastsupporting
confidence: 74%
“…By monitoring the rescue of the PMA1 mRNA level in different deletion strains, we showed that the targeting and degradation of Rho-induced aberrant mRNPs by Rrp6 is stimulated by the cofactors Rrp47 and Mpp6 as well as the TRAMP complex [13]. An interesting finding made in those studies, which was also reported by others [14][15][16], is that Rrp47 plays an important role in a mutual protein stabilization with Rrp6, highlighting a close physical association between the two protein partners [16]. In effect, removal of one partner by gene deletion induces a depletion of the other partner by more than 90% [13].…”
Section: Rho-based Perturbation Of Mrnp Biogenesis In Yeastsupporting
confidence: 74%
“…Although CSL4 is essential in yeast, mutant strains with truncated versions that lack NTD or S1 domain are viable, and the zinc-ribbon domain is not essential in vivo. In addition it has been shown that Csl4 is not stably associated with exosomes in vitro (61). Absence of csl4 has also been reported in another protozoan parasite, Giardia lamblia (37), and may be a more common feature in early eukaryotic evolution.…”
Section: Discussionmentioning
confidence: 98%
“…This predicts that the rrp44-da mutation may show genetic interactions with mutations of nuclear RNA exosome cofactors, such as Rrp6. Rrp6 is an additional exonuclease that associates with the RNA exosome in the nucleus, but also has non-catalytic roles including mediating interactions with additional cofactors such as Rrp47 and Mtr4 (Butler and Mitchell, 2011; Feigenbutz et al, 2013; Schuch et al, 2014). As expected, the rrp44-da mutation shows a synthetic growth defect with rrp6Δ (Figure 3B) confirming that the Rrp44 da conformation is important for the nuclear functions of the RNA exosome.…”
Section: Resultsmentioning
confidence: 99%